The effect of nano zinc oxide on freeze-thaw resistance of 3D-printed geopolymer mortars - Tanyildizi, Harun; Seloglu, Maksut; Coskun, Ahmet (Elsevier, 2024)
The aim of this study was to investigate the freeze-thaw resistance of 3D-printed geopolymer mortars containing nano zinc oxide (nano-ZnO). Metakaolin (MK) and fly ash (FA) were selected as binders in the geopolymer mortar. The mixes containing 0 %, 0.25 %, 0.5 %, and 0.75 % nanoZnO were prepared. The viscosity, setting time, buildability, and flow experiments were made to determine the fresh properties of the samples. Then, 40 x 40 x 160 mm samples for hardened properties were produced using the 3D printer, and they were cured at 20 +/- 2 degrees C for 28 days. In this study, the 3D-printed geopolymer mortars were subjected to freeze-thaw cycles according to TS EN 15177 standard. Finally, ultrasonic pulse velocity (UPV), the weight change, flexural strength, and compressive strength of 3D-printed geopolymer mortar samples exposed to freeze- thaw cycles were determined. Also, the microstructure of 3D-printed geopolymer mortar samples was analyzed using X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy- dispersive X-ray (EDX) analysis. This study found that the 3D-printed geopolymer mortars containing 5 % nano-ZnO had the highest resistance to freeze-thaw, with a compressive strength retention rate of 95.72 %. Thus, this study showed that the 3D-printed geopolymer mortars containing ZnO were resistant to freeze-thaw.
Keywords: 3D-printed geopolymer mortar; Nano-ZnO; Rheology; Freeze-thaw resistance; Mechanical strength